Toxicite potentielle des sediments marins et estuariens contamines : evaluation chimique et biologique, biodisponibilite des contaminants sedimentaires - Geffard, Olivier (Bordeaux 1, 2001)
Marine and estuarine sediments concentrate various pollutants. Thus, they can constitute a risk of contamination for aquatic organisms, and cause a public health problem. The potential toxicity of various sediments was studied by different bioassays and by assessing the bioavailability of polycyclic aromatic hydrocarbons (PAH) and metals they contained. Among the various stages of development investigated in oysters, Crassostrea gigas, and in sea urchins, Paracentrotus lividus, oyster embryos and larvae proved to be the most sensitive and useful tool for the evaluation of sediment effects on benthic organisms (whole sediment treatment embryotoxicity test) as well as on pelagic species (elutriate treatment; embryotoxicity and larval growth tests). Environmental assessments should be conducted with fresh sediments. Bioavailability of PAHs and metals from sedimentary origin were assessed by studying contaminant bioaccumulation and metallothionein induction (in the case of sediments with metal contamination) in C. gigas and mussel, Mytilus galloprovincialis larvae. These tools were found to be more sensitive and giving precocious responses, than simple bioassays, to assess the biological responses towards contaminants. Furthermore they make possible to correlate pollution effects at molecular (metallothionein), cellular (bioaccumulation), individual (larval abnormalities and larval growth) and population levels (since contaminant effects on the reproductive stages impede the population dynamics of species). These investigations have led us to the propose of a procedure for the evaluation of sediment quality in biomonitoring studies. The sensitivity and advantage of oyster embryos and larvae in marine ecotoxicology were confirmed, by their use in situ bioassays. Les sédiments marins et estuariens sont un réservoir pour de nombreux polluants, constituant non seulement une source de contamination pour les organismes aquatiques, mais pouvant également poser un problème de santé publique. La toxicité potentielle de ...